The process of highly effective coaching an evidence-based framework - Hicks, Robert F. (Routledge, Taylor & Francis Group, 2017)
The Process of Highly Effective Coaching offers a unique blend of theory and practical methods for conducting effective coaching conversations. It provides an umbrella under which all of the major conceptual models for helping people change can not only coexist but work together. In addition to using this integrative approach, The Process of Highly Effective Coaching presents a framework for conducting coaching conversations and for relating the coaching process to the coaching competencies defined by the International Coach Federation, the largest coach-credentialing organization in the world.